Perkembangan Cybercrime dan Dampaknya terhadap Keamanan Nasional Indonesia: Analisis Ancaman Asimetris dan Strategi Ketahanan Siber - Gilang Rizki Aji Putra (BULETIN ADALAH, 2023)
Cybercrime has transformed from conventional computer-based offenses into a multidimensional threat targeting critical infrastructure, political stability, and national economic resilience. This article analyzes the evolving modus operandi of cybercrime in Indonesia over the past decade and assesses its impact on national security within a multidimensional security framework. Using normative legal research with conceptual, statutory, and case study approaches, the study finds that cybercrime in Indonesia has progressed from online fraud and hacking to structured cyberattacks against national data infrastructure, digital espionage, and large-scale disinformation campaigns threatening political stability. The analysis indicates that existing regulatory frameworks, including the Electronic Information and Transactions Law and the Personal Data Protection Law, as well as institutional bodies such as the National Cyber and Crypto Agency (BSSN), remain largely reactive and insufficient to address the asymmetric and transnational nature of these threats. The article concludes that cybercrime constitutes an existential challenge to Indonesia’s digital sovereignty and requires comprehensive legislative, institutional, and regional intelligence cooperation reforms. Keywords: Cybercrime, National Security, Asymmetric Threats, BSSN, Hybrid Warfare.